TERATOGENEOUS EFFECTS OF GYNURA PROCUMBENS (LOUR.) MERR. ETHANOL EXTRACT AGAINST MUS MUSCULUS FETAL - Uthia, Rahimatul; Anggraini, Riza; Fauziah, Fitra; Rz, Ira Oktaviani (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Kemenkes Riau, 2020)
This study looked at the teratogenous effects of ethanol extracts of Gynura procumbens (Lour.) Merr. on the white mice fetus. Experimental animals consisted of 24 mices, 4 male mices and 20 female mices, divided into 4 groups, namely the negative control group, ethanol extracts of Gynura procumbens (Lour.) Merr. 150 mg/kg BW; 300 mg/kg BW; and 600 mg/kg BW. Provision is made from the 6th day until the 15th day of pregnancy. Laparactomy is carried out on the 18th day of pregnancy. The parameters observed were body weight of mices, number of fetuses, average fetal weight, and macroscopic observation of the fetus. The results showed that the parent's body weight, number of fetuses, and average fetal weight were significantly different (sig <0.05). Macroscopic observation of the fetus obtained slow growth in ethanolic extracts dose of 600 mg/kgBW. This study can be concluded that the ethanol extract of Gynura procumbens (Lour.) Merr.has a teratogenic effect on the fetus of white mice.